2004
DOI: 10.1074/jbc.m410247200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Interaction at an Iron-Sulfur Face of the FeMo-cofactor during Nitrogenase Catalysis

Abstract: Nitrogenase catalyzes biological dinitrogen fixation, the reduction of N 2 to 2NH 3 . Recently, the binding site for a non-physiological alkyne substrate (propargyl alcohol, HC'C-CH 2 OH) was localized to a specific Fe-S face of the FeMo-cofactor approached by the MoFe protein amino acid ␣-70Val . Here we provide evidence to indicate that the smaller alkyne substrate acetylene (HC'CH), the physiological substrate dinitrogen, and its semi-reduced form hydrazine (H 2 N-NH 2 ) interact with the same Fe-S face of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
160
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 32 publications
7
160
0
Order By: Relevance
“…From the results in Figure 3B, a minimum V max for diazene reduction by nitrogenase is found to be 400 nmol NH 3 /min/ mg MoFe protein. This value compares favorably with the V max for N 2 reduction by nitrogenase determined in a parallel experiment of 600 nmol NH 3 /min/mg MoFe protein (35). Likewise, an upper limit on the K m for diazene is calculated to be 4.5 mM, compared to the K m for N 2 of 60 μM (35).…”
Section: Diazene Is a Substrate For Nitrogenasesupporting
confidence: 70%
“…From the results in Figure 3B, a minimum V max for diazene reduction by nitrogenase is found to be 400 nmol NH 3 /min/ mg MoFe protein. This value compares favorably with the V max for N 2 reduction by nitrogenase determined in a parallel experiment of 600 nmol NH 3 /min/mg MoFe protein (35). Likewise, an upper limit on the K m for diazene is calculated to be 4.5 mM, compared to the K m for N 2 of 60 μM (35).…”
Section: Diazene Is a Substrate For Nitrogenasesupporting
confidence: 70%
“…Significantly, however, the nonheterocyst nitrogenase of this strain, which is expressed mainly in vegetative cells under anaerobic conditions, is incompatible with O 2 -evolving photosynthesis and thus requires continuous anaerobic conditions along with a supply of exogenous reducing sugars for H 2 production. Substitutions of selected amino acids in the vicinity of the FeMo-co active site within Azotobacter vinelandii nitrogenase were shown to eliminate or greatly diminish N 2 fixation while, in some cases, allowing for effective proton reduction (2,10,17,27,36,44,45,48). Therefore, certain amino acid exchanges near FeMo-co might produce variant MoFe proteins in heterocyst-forming Anabaena that redirect the electron flux through the enzyme preferentially to proton reduction so as to synthesize more H 2 in the presence of N 2 in an aerobic environment.…”
mentioning
confidence: 99%
“…The nitrogenase-related (nif) genes are specifically expressed in heterocysts which lack O 2 -evolving photosystem II activity and are surrounded by a thick cell envelope composed of glycolipids and polysaccharides that impede the entry of O 2 (56). Vegetative cells perform oxygenic photosynthesis and fix CO 2 . Heterocysts obtain carbohydrates from those cells and, in turn, provide them with fixed nitrogen.…”
mentioning
confidence: 99%
“…A number of different interaction sites can be considered upon inspection of the structure of FeMo-cofactor and calculations have been reported that support a number of different binding sites [4,12]. In our earlier studies, we began to localize the site of alkyne substrate interactions with FeMo-cofactor to one Fe-S face that includes Fe atoms numbered 2, 3, 6 and 7 [2,[13][14][15][16][17][18][19][20]. Analysis of the capacity of MoFe proteins having amino acid substitutions for residues that approach this Fe-S face to reduce a range of substrates has indicated that this face might provide the only site for substrate binding and reduction.…”
Section: Introductionmentioning
confidence: 99%
“…By using the amino acid substitution approach, conditions were also developed that allowed trapping and characterization of an intermediate that accumulates during the reduction of propargyl alcohol by the α-70 Ala -substituted MoFe protein [18]. Characterization of this intermediate by EPR and 13 C-and 1/2 H-electron nuclear double resonance (ENDOR) spectroscopies were interpreted to indicate side-on binding of a 2e − /2H + reduced allyl alcohol species (H 2 C=CH-CH 2 OH) that is bound to FeMo-cofactor through a single Fe atom [17]. The effect of pH dependence on the capacity of the α-70 Ala MoFe protein to reduce either propargyl alcohol or propargyl amine (HC≡C-CH 2 NH 2 ) further localized the proposed binding site to Fe atom 6 [16] within FeMo-cofactor (Figure 1).…”
Section: Introductionmentioning
confidence: 99%